Relationship Of Exposure To Cigarette Smoke In Pregnant Mothers To The Weight Of Newborn In Bhayangkara Palembang Hospital In 2021 - Agustin, Ismar; Endriyani, Sri; rehana, Rehana; Utari, Tri (UIMA Press, 2021)
Abstrak Background:. Exposure to cigarette smoke can affect low birth weight in mothers who are exposed to cigarette smoke. Low birth weight (LBW) babies are babies with a birth weight of less than 2500 grams. Objectives: To analyze the relationship between age, parity, gestational distance, education, occupation, exposure to cigarette smoke on the weight of newborns in mothers who gave birth. Methods: This research is analytic with a cross-sectional approach. The population and sample are 50 using total sampling technique. Results: The results of the statistical test showed that the variables that were statistically significantly related to the birth weight of newborns were age, parity, education, and exposure to cigarette smoke with ap value <0.05, while the variable distance between pregnancy and occupation did not have a significant relationship. with p value> 0.05. Conclusion: there is a significant relationship between exposure to cigarette smoke and the weight of newborns at Bhayangkara Hospital Palembang in 2021. Keywords: low birth weight, pregnant, passive smoking